A transgenic zebrafish model expressing KIT‐D816V recapitulates features of aggressive systemic mastocytosis. (2nd July 2014) - Balci, Tugce B.; Prykhozhij, Sergey V.; Teh, Evelyn M.; Da'as, Sahar I.; McBride, Eileen; Liwski, Robert; Chute, Ian C.; Leger, Daniel; Lewis, Stephen M.; Berman, Jason N.
Summary Systemic mastocytosis (SM) is a rare myeloproliferative disease without curative therapy. Despite clinical variability, the majority of patients harbour a KIT‐D816V mutation, but efforts to inhibit mutant KIT with tyrosine kinase inhibitors have been unsatisfactory, indicating a need for new preclinical approaches to identify alternative targets and novel therapies in this disease. Murine models to date have been limited and do not fully recapitulate the most aggressive forms of SM. We describe the generation of a transgenic zebrafish model expressing the human KIT‐D816V mutation. Adult fish demonstrate a myeloproliferative disease phenotype, including features of aggressive SM in haematopoeitic tissues and high expression levels of endopeptidases, consistent with SM patients. Transgenic embryos demonstrate a cell‐cycle phenotype with corresponding expression changes in genes associated with DNA maintenance and repair, such as reduced dnmt1. In addition, epcam was consistently downregulated in both transgenic adults and embryos. Decreased embryonic epcam expression was associated with reduced neuromast numbers, providing a robust in vivo phenotypic readout for chemical screening in KIT‐D816V‐induced disease. This study represents the first zebrafish model of a mast cell disease with an aggressive adult phenotype and embryonic markers that could be exploited to screen for novel agents in SM.